Financial Distress Prediction Model Using Financial Ratios and Cash Flow: A Quantitative Approach (Sudy for retail companies listed on the IDX for the 2020-2024 period) - Hanafi, Mukhlis; Purwanto, Setiyo (PT Mattawang Mediatama Solution, 2025)
This study analyzes the influence of financial ratios and cash flows on financial distress conditions in retail companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The independent variables tested included Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Cash Flow from Operations (CF), with Financial Distress (FD) measured using the Altman Z-Score. The method used is multiple linear regression. The research uses a quantitative approach with secondary data from the financial statements of retail companies listed on the IDX during 2020–2024. The sample was selected by purposive sampling based on the criterion of declining profits for two consecutive years. Financial distress is measured with the Altman Z-Score. Data analysis uses multiple linear regression to test the influence of independent variables on financial distress. Multicollinearity, normality, and heteroscedasticity tests were performed to ensure the validity of the model. The results showed that CR, DER and CF had no significant effect on FD, only ROA had an effect on FD. These findings confirm the importance of managing financial ratios, especially on asset ratios, to reduce the risk of financial distress, which is a reference for managers and investors in financial decision-making.